FENOMENA BAHASA GAUL SEBAGAI KREATIVITAS LINGUISTIK DALAM MEDIA SOSIAL INSTAGRAM PADA ERA MILENIAL - Syafi' Junadi; Rani Karomatul Laili (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
The problems analyzed in the thesis of the phenomenon of slang as linguistic creativity in Instagram social media in this millennial era are numerous. To obtain more linear and specific analysis results, the problems studied in this scientific paper study must be limited to the characteristics of the slang on Instagram social media, the equivalent vocabulary of slang with Indonesian on Instagram social media and the process of forming the lingual unit of slang in the media social Instagram and the positive and negative impacts of using slang in the millennial era. The research method used in this thesis research is a qualitative descriptive research method with phenomenological qualitative techniques. In this study, the collection of data and information was obtained through informants, namely by means of observation or observation. The results of the data obtained through data collection techniques are then compiled to form a systematic report, namely Instagram account owners in the millennial era.